Pengaruh Lingkungan Kerja dan Komitmen Organisasi Terhadap Produktivitas Kerja Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada PDAM Tirta Bara Kabupaten Banjarnegara Tahun 2022 - Revaldo Juan Wicaksana (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The aim of this research is to describe the results of the analysis of the influence of the work environment and organizational commitment on work productivity through job satisfaction. The research method uses a quantitative approach, by determining the sample or data source using the Slovin formula with an error rate of 5% as a computational tool to measure the sample size because it is known that the population is more than 100 respondents. Test the instrument using validity tests and reliability tests. Meanwhile, hypothesis testing uses the R square test, path analysis test, model fit test. The results of research on employees of PDAM Tirta Bara Banjarnegara Regency using the SmartPLS 3 calculation tool and quantitative research methods, it can be seen that the work environment has no effect on work productivity, the work environment has an effect on job satisfaction, organizational commitment has an effect on job satisfaction, organizational commitment has an effect on work productivity, job satisfaction influences work productivity, the work environment influences work productivity through job satisfaction, and organizational commitment influences work productivity through job satisfaction. As an agency that depends on employee performance, PDAM Tirta Bara Banjarnegara Regency needs to pay attention to several aspects, such as a conducive work environment needed to optimize employee performance, commitment from the organization in respecting what employees have given to the company, positive job satisfaction is also needed to create high employee work productivity.